A Netnographic Study: Construction of AI-Based Learning Media Training on pintar.kemenag.go.id - Pranajaya, Syatria Adymas; Cahyadi, Ani; Nasir, Muhammad; Riwanda, Agus; Pratama, Dinar (Sekolah Tinggi Ilmu Syariah Ummul Ayman Pidie Jaya, 2024)
This research was conducted to find out how the construction carried out by community participants of Artificial Intelligence (AI)-based Learning Media Training on the pintar.kemenag.go.id application or website facilitated by Badan Litbang dan Diklat Kementerian Agama RI as a virtual training medium. Using the netnography method, researchers try to reveal and analyze the way community participants present the